Pengaruh Persepsi Variasi Produk, Cita Rasa, dan Experiential Marketing Terhadap Loyalitas Konsumen pada Coffee Shop Kogu di Kota Malang (Studi Kasus pada Konsumen Coffee Shop Kogu di Kota Malang) - Mahfudhah, Nisrina Hasna; Basalamah, Muhammad Ridwan; Amin, Muh Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research was conducted with the aim of analyzing the extent of the cause-and-effect relationship between variables of Perception of Product Variety, Taste, and Experiential Marketing on Consumer Loyalty at Kogu Coffee Shop in Malang City. This research uses quantitative methods with purposive sampling technique. The research sample used was Kogu Coffee Shop consumers in Malang City with a total of 90 respondents who provided research data through a questionnaire. Data analysis was carried out using SPSS 26 to carry out instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient tests (Adjusted R2). This research shows that simultaneously Perception of Product Variety, Taste, and Experiential Marketing have a significant effect on Consumer Loyalty. Partially, Perception of Product Variety has a significant effect on Consumer Loyalty, Taste has a significant effect on Consumer Loyalty, and Experiential Marketing has a significant effect on Consumer Loyalty. Keywords: Perception of Product Variety, Taste, Experiential Marketing, and Consumer Loyalty